The Gender Discrimination in Indonesian Literature Works: A Case Study of Translation - Mangatur Rudolf Nababan; Riyadi Santosa; Sri Samiati Tarjana; Nunun Tri Widarwati (Script Journal: Journal of Linguistics and English Teaching, 2021)
Background: Although many kinds of research on gender discrimination have been made, empirical research on this matter under the perspective of translation technique is still rare. Therefore, this present research aimed to study gender discrimination in three novels authored by Pramoedya Ananta Toer and how gender discrimination is translated into English. Methodology: This case study was applied in three novels written by Pramoedya Ananta Toer, Anak Semua Bangsa, Rumah Kaca, and Jejak Langkah. The data were collected through observations and Focus Group Discussion (FGD). The data were analyzed using thematic analysis. Findings: The results showed that gender discrimination in the three novels was subordination, stereotype, marginalization, workload, and violence. Gender discrimination is translated using established equivalence, explicitation, modulation, paraphrase, implicitation, addition, transposition, reduction, compensation, discursive creation, pure borrowing, deletion, generalization, and particularization. Conclusion: This research reveals that gender discrimination is a phenomenon that commonly occurs in the world community. The research implications are also discussed either empirically or practically at the end of this article.